The investigation with technology understood from the point of view of the Mathematics teacher for their practice - Carolina Cordeiro Batista; Rosa Monteiro Paulo (Universidade Cruzeiro do Sul, Ensino de Ciências e Matemática, 2023)
This article aims to explain how a technology investigation work is understood by a mathematics teacher willing to analyze the lived experience whitin this type of practice. Based on the lesson study perspective and a phenomenological view of knowledge constitution, within a group of teachers we discussed ways of working mathematics content with investigation tasks and the GeoGebra software. The teachers performed the tasks with their students and analyzed their lived experience. The discussions were recorded and transcribed, constituting data for a doctorate research conducted under a phenomenological qualitative approach. The results show that teachers understand that: students define research strategies and mobilize previous knowledge; technology favors the understanding of content and contributes to the expression of what is seen in the software; and the investigation carried out by the students subsidizes the reorganization of the teachers' actions.